2016
DOI: 10.1016/j.apnr.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of routine episiotomy in primigravida women in Oman

Abstract: The rate of episiotomies was higher than other similar contexts. An urgent intervention is necessary to curb this excessive practice, and create a culture of evidence-based practice to deal with misleading perceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
22
4
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 6 publications
7
22
4
4
Order By: Relevance
“…Binary logistic regression also showed that midwives who had a bachelor's degree and obstetricians who had a doctor's degree were most likely to perform episiotomies on primiparas. Our findings are consistent with those of Al‐Ghammari et al., which found that bachelor's degree‐holders were 2.26 times more likely than diploma‐holders to perform an episiotomy. It could be attributed to the possibility that highly degree holders may be subject to more difficult deliveries.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Binary logistic regression also showed that midwives who had a bachelor's degree and obstetricians who had a doctor's degree were most likely to perform episiotomies on primiparas. Our findings are consistent with those of Al‐Ghammari et al., which found that bachelor's degree‐holders were 2.26 times more likely than diploma‐holders to perform an episiotomy. It could be attributed to the possibility that highly degree holders may be subject to more difficult deliveries.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of episiotomy in our WC cohort was 44% which was generally lower than other Asian countries reported rates of 63.4% (Indian), 66% (Oman), and 75.1% (Yemen) . The WC episiotomy rate was generally higher than that in America (6.7%), Australia (17.2%), and Spain (30.0%); and comparable to one German study reporting 37.7% and 41.4% in Jordan .…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…[8] Unfortunately, obstetricians usually carry out episiotomies habitually as it was thought to hasten the second phase of delivery and decrease the danger of impulsive perineal damaging. [9] Countless interventions are obtainable to support the episiotomy wound healing process during puerperium. They include: using cold compresses, topical use by dry heat (Infrared therapy), sitz bath, carrying out of kegel's exercise and perineal care.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Of note, most studies reveal overall rates of episiotomy higher than 10%. 20,28,[29][30][31][32][33][34][35][36] The wide variation in episiotomy rates among countries may be attributed to the lack of guidelines for the performance of episiotomy, which makes the decision for the procedure a clinical judgment. 32 We know the decision to perform interventions such as episiotomies may be improved by the use of partograms in labor assistance.…”
mentioning
confidence: 99%